PENGARUH PARTISIPASI DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL: KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING - Yulia Putri; Novita (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2020)
This study aims to determine: (1) Effect of Budget Participation on Managerial Performance, (2) Effect of Organizational Commitment on Managerial Performance, (3) Effect of Organizational Commitment to Moderate the Relationship Between Budget Participation and Managerial Performance. The research data was collected using questionnaire techniques. The number of samples in this study were 42 respondents Structural Officials at one of the private universities in Jakarta. The sampling technique uses purposive sampling. Data analysis method uses Partial Least Square (PLS) method, the analysis is carried out through three stages, namely outside model analysis, internal model analysis, and hypothesis testing. The results of this study indicate the effect of budgeting participation has a positive and significant effect on managerial performance, the second hypothesis shows organizational commitment has a positive and significant effect on managerial performance, and the third hypothesis indicates that moderate organizational commitment has a positive influence and significant influence on participation participation relationships budget with managerial performance.